Analysis of the dynamics of biological productivity of saxaul forests in Ile-Balkhash region (Experimental biology, 2015)
The paper presents the study of the biological productivity of saxaul forests of Ile-Balkhash region. There are analyzed the age dynamics of biomass of a tree of black saxaul under various conditions of groundwater. Biomass changes at the level of groundwater 3-4 m is a linear relationship. Biomass changes at the level of groundwater 5-6 m is an exponential dependence. With increasing age, increasing biomass, respectively. However, saxaul biomass grown under high ground water table above. Revealed the positive effect of close groundwater to the annual increase of biomass in forest ecosystem.. On the basis of changes in biological productivity, the annual increase in biomass, as well as a variety of growing conditions of saxaul forests given the recommendations on forest management adapted to the Ile-Balkhash region. The region has been allocated 3 areas: forestry reclamation, , agroforestry economic and agroforestry.
Keywords: Biological productivity; saxaul; age dynamics; biomass; forestry